JURNALISME WARGA SEBAGAI KATALISATOR KOMUNIKASI POLITIK YANG BERIMBANG - Petrus Imam Prawoto Jati; Muhammad Sulthan (Jurnal Ilmu Komunikasi Acta Diurna, 2013)
In a democratic political life , people are required to behave actively in political processes . Socie-ty either consciously or unconsciously , formally or informally , often get involved in the communi-cation processes that involves analysis and study of political communication . Media thus becomethe channel that connects the political interests either vertically or horizontally . Media becomesthe container in political life as a place for people , politicians and rulers to meet . Most politicalcommunications in the media , conducted by journalists from major media or mainstream media .The active role of the journalist is to seek , cultivate and broadcast informations . During its devel-opment , in line with the acceleration of technological development , this journalistic activities canalso be done by the general public . This phenomenon is called Jurnalisme Warga , often calledcitizen journalism , participatory journalism or public journalism . Not mutually exclusive , eventhe mainstream media and citizen journalism can be complementary , mutually controlling andfurther could be expected to achieve a balance in establishing the objectivity of the nation politi-cal life reality. Opinions or voices that born from Citizen Journalism will be heard by both partieseither by society itself horizontally and up to government vertically . If good journalism ethicsguide could be implemented well, this Citizen Journalism will be able to perform a function as acatalyst of balanced political communication.